Food packaging materials with polyphenols as active compounds - Jakobek Barron, Lidija (Array, 2019)
Packaging is the basis for good preservation of food quality and food safety. A relatively new type of packaging is active packaging, which attracts attention due to its many positive features. Especially interesting materials for active packaging are biodegradable materials. Not only can these materials play the role of the carrier of the active component, but they are also more rapidly degradable and edible, which gives additional positive properties. Natural compounds such as polyphenolic compounds can be added to the packaging materials as an active compound. Although the addition of polyphenols to the active packaging is in the research phase, it is evident from the results so far that such materials have the potential for commercial use in food packaging. The aim of this paper is to briefly describe the use of polyphenolic compounds as active ingredients in active packaging.